Role of GSPT1 and GSPT2 polymorphisms in different outcomes upon Hepatitis B virus infection and prognosis to lamivudine therapy. Issue 3 (29th March 2019) - Liu, Wenxuan; Ma, Ning; Gao, Xia; Liu, Wencong; Jia, Jinhai; Tang, Longmei; Li, Man; Yang, Lei; Li, Tao; Yan, Lina; Zhang, Xiaolin; Yu, Fengxue
Abstract : Purpose. ERF3, having been found expressing differently in liver tissues in our previous work, including eRF3a and eRF3b, which are structural homologs named GSPT1 and GSPT2 . Recent studies have indicated that eRF3b involved in the development and proliferation of HepG2 cell, and eRF3a may be associated with tumor susceptibility. Based on this, we tested the effects of GSPT1 and GSPT2 single-nucleotide polymorphisms for all major Hepatitis B virus (HBV) outcomes and lamivudine (LAM) treatment in Han Chinese. Method. A total of 1649 samples were enrolled, and peripheral blood samples were collected in the present study. The single-nucleotide polymorphisms in the GSPT1 and GSPT2 region were genotyped using MALDI-TOF MS. Results. Our study demonstrated there was no obvious relevance of either GSPT1 -rs33635 or GSPT2 -rs974285 polymorphisms with HBV susceptibility, spontaneous recovery, and development of HBV-related diseases. However, we showed for the first time to our knowledge that GSPT1 -rs33635C was a predictor for LAM therapy (viral response: odds ratio (OR) = 2.436, P =0.022; biochemical response: OR = 3.328, P =1.73 × 10 −4 ). Conclusions. These findings might provide potential implications for therapeutic guidance.